Cover Image. Issue 6 (19th December 2020) - Unknown
Abstract : In the article e10136, Alfréd Menyhárd and colleagues study the crystallization of isotactic polypropylene (iPP) in the presence of 50 ppm nucleating agent using polarized light microscopy. During the sample preparation, the polymer melt is quenched from 240 °C to 135 °C, thus the recrystallization and self‐organization of the nucleating agent, as well as the crystallization of the polymer, occur simultaneously. At the center of the micrograph a "microcrystalline" structure is developed, which consists of the small α‐crystals overgrown by the β‐iPP matrix. (doi.org/10.1002/pcr2.10136 ) Abstract : In the article e10136, Alfréd Menyhárd and colleagues study the crystallization of isotactic polypropylene (iPP) in the presence of 50 ppm nucleating agent using polarized light microscopy. During the sample preparation, the polymer melt is quenched from 240 °C to 135 °C, thus the recrystallization and self‐organization of the nucleating agent, as well as the crystallization of the polymer, occur simultaneously. At the center of the micrograph a "microcrystalline" structure is developed, which consists of the small α‐crystals overgrown by the β‐iPP matrix. (doi.org/10.1002/pcr2.10136 )